Silicon-carbon composite material for lithium ion battery and preparation method of silicon-carbon composite material
By using molybdenum-doped silicon-carbon composite materials and electrospinning methods in the negative electrode materials of lithium-ion batteries, the battery failure problem caused by volume expansion of silicon-carbon materials is solved, and the effect of improving lithium storage activity and cycle stability is achieved, while having the advantages of low cost and environmental protection.
Patent Information
- Application Number
- CN202411747919.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-21
AI Technical Summary
The existing lithium-ion battery negative electrode material, silicon carbon material, expands and contracts due to high volume expansion, causing the material to powder and fall off, and thus fails the battery.
Porous carbon nanofibers are prepared by electrospinning method using molybdenum-doped silicon-carbon composite materials, and the silicon nanoparticles and molybdenum oxide nanoparticles are uniformly dispersed for use in the negative electrode of lithium-ion batteries.
It improves lithium storage activity, buffers the volume expansion of the electrode during the deintercalation of lithium, and improves the circulation stability of the material. At the same time, the preparation method is simple, low cost, low energy consumption and environmentally friendly.
Smart Images

Figure CN119673989A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a molybdenum-doped silicon-carbon composite material for a negative electrode of a lithium ion battery and a preparation method thereof. Background Art
[0002] Throughout the history of battery development, lithium-ion batteries, as a major form of new energy, have received widespread attention and developed rapidly because of their high volume-to-energy and mass-to-energy ratios, rechargeability, and pollution-free. At present, the development of the telecommunications and information markets, especially the extensive use of mobile phones and laptops, has brought market opportunities to lithium-ion batteries. Today, lithium-ion batteries are widely used in the consumer electronics field and the electric vehicle industry, affecting almost everyone's life.
[0003] As people's requirements for battery energy density are getting higher and higher, traditional lithium-ion batteries can no longer meet people's requirements, and high energy density batteries have received more and more attention. The energy density of lithium-ion batteries mainly depends on the positive and negative electrode materials of the battery. The improvement and development of positive and negative electrode materials are the key to improving battery energy density. Graphite, as a traditional lithium-ion negative electrode material, has been widely used in various industries because of its high cycle efficiency and good cycle performance. However, its theoretical capacity is only 372mAh / g, which can no longer meet people's requirements for high energy density. Therefore, the development of new high energy density negative electrode materials has become a key technology to improve lithium-ion batteries.
[0004] Silicon-carbon negative electrode material is a new type of negative electrode material for lithium batteries, which combines the high energy density of silicon materials and the good conductivity of carbon materials. Silicon-carbon materials have higher safety and application prospects because of their theoretical capacity of up to 4200mAh / g and low lithium insertion potential. However, the volume change rate of silicon materials during lithium insertion and extraction is as high as 320%, which is much higher than the 12% of carbon materials. This huge volume change will cause the expansion and contraction of silicon-carbon negative electrode materials, which will lead to the pulverization and shedding of negative electrode materials, and eventually cause the battery to lose electrical contact and fail completely.
[0005] Therefore, how to alleviate the high expansion rate of silicon-carbon negative electrodes is the main challenge facing the current silicon-carbon negative electrode material preparation technology. The existing solutions mainly alleviate the expansion rate by changing the structural design of silicon-carbon negative electrode materials. For example, the size of silicon materials can be reduced to the nanoscale through nano-processing to reduce its volume change rate. In addition, the structural stability of silicon-carbon negative electrode materials can be improved by introducing other elements or compounds. However, these methods often require complex processes and expensive equipment, and may affect the electrochemical properties of silicon-carbon negative electrode materials. Summary of the invention
[0006] In order to solve the problems of low lithium storage activity and large volume expansion of the above-mentioned silicon-carbon materials, the object of the present invention is to provide a molybdenum-doped silicon-carbon composite material for lithium-ion battery negative electrode and a preparation method thereof.
[0007] The present invention dissolves molybdenum acetylacetonate and polyacrylonitrile in N,N-dimethylformamide, then dissolves nano silicon particles and polyacrylonitrile in N,N-dimethylformamide, fully mixes and stirs the two solutions, uses the obtained uniform solution as a precursor solution, prepares multi-porous carbon nanofibers by an electrostatic spinning method, and finally, dries and calcines the obtained composite material for the negative electrode of a lithium ion battery; that is, the molybdenum-doped silicon-carbon composite material for the negative electrode of a lithium ion battery includes multi-porous carbon nanofibers, silicon nanoparticles and molybdenum oxide nanoparticles, and the silicon nanoparticles and molybdenum oxide nanoparticles are uniformly dispersed and attached to the multi-porous carbon nanofibers. The composite material can not only improve the lithium storage activity, but also buffer the volume expansion of the silicon-carbon material in the process of lithium insertion and extraction of the electrode, and improve the cycle stability of the material. In addition, the preparation method has the characteristics of simple preparation and easy operation, low cost, low energy consumption and no pollution to the environment.
[0008] In the above molybdenum-doped silicon-carbon composite material, the molybdenum content is 0.5%-2%, and the silicon content is 10%-70% by mass fraction.
[0009] Preferably, in the above molybdenum-doped silicon-carbon composite material, the molybdenum content is 0.7%-1.8%, and the silicon content is 15%-55%, calculated by mass fraction.
[0010] More preferably, in the above molybdenum-doped silicon-carbon composite material, the molybdenum content is 0.9%-1.6%, and the silicon content is 20%-50%, calculated by mass fraction.
[0011] The present invention also provides a method for preparing the molybdenum-doped silicon-carbon composite material for a negative electrode of a lithium-ion battery, comprising the following steps:
[0012] (1) dissolving molybdenum acetylacetonate and polyacrylonitrile in N,N-dimethylformamide to obtain a first solution, and dissolving nano-silicon particles and polyacrylonitrile in N,N-dimethylformamide to obtain a second solution;
[0013] (2) mixing the first solution and the second solution and stirring them thoroughly to obtain a uniform mixed solution as a precursor solution for electrospinning;
[0014] (3) The electrospinning precursor solution is drawn out through a syringe equipped with a blunt-tipped needle, and a DC power supply is used to provide a voltage between the aluminum foil and the needle tip, so that the solution is ejected from the metal needle and the material is collected on the aluminum foil;
[0015] (4) The material collected on the aluminum foil is degassed, dried and calcined to obtain the product.
[0016] In step (2), in the mixed solution, the mass percentage concentration of molybdenum acetylacetonate is 0.5%-2%, the mass percentage concentration of polyacrylonitrile is 19%-44.75%, and the mass percentage concentration of nano-silicon particles is 10%-70%; the molecular weight of polyacrylonitrile is selected from any one of 100k, 150k, 200k, and 250K; in step (3), the feed rate of the electrospinning precursor solution is 0.1-5ml / h, the electrospinning height is 15-30cm, and the electrospinning voltage is 15-25kV; in step (4), the degassing and drying temperature is 200℃-360℃; and the calcination temperature is 600℃-850℃.
[0017] The present invention also provides an electrode, which includes the above-mentioned molybdenum-doped silicon-carbon composite material for the negative electrode of a lithium ion battery or the molybdenum-doped silicon-carbon composite material for the negative electrode of a lithium ion battery prepared using the above-mentioned preparation method of the molybdenum-doped silicon-carbon composite material for the negative electrode of a lithium ion battery.
[0018] The present invention also provides a battery, which comprises the above-mentioned electrode.
[0019] Beneficial effects: The carbon nanofibers of the molybdenum-doped silicon-carbon composite material for the negative electrode of a lithium-ion battery of the present invention have a pore structure, and molybdenum oxide nanoparticles and silicon nanoparticles are uniformly distributed in the carbon nanofibers; the composite material can not only improve the lithium storage activity, but also buffer the volume expansion of the silicon-carbon material during the lithium insertion and extraction process of the electrode, thereby improving the cyclic stability of the material; in addition, the preparation method of the molybdenum-doped silicon-carbon composite material has the advantages of being simple and easy to operate, low cost, low energy consumption, and no pollution to the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is an electron microscope scanning image of the molybdenum-doped silicon-carbon composite material of the present invention. DETAILED DESCRIPTION
[0021] The present invention will be further described in detail below by way of examples, but the present invention is not limited to the examples.
[0022] The present invention provides a molybdenum-doped silicon-carbon composite material for a negative electrode of a lithium-ion battery, comprising a multi-porous carbon nanofiber, silicon nanoparticles and molybdenum oxide nanoparticles, wherein the silicon nanoparticles and the molybdenum oxide nanoparticles are uniformly dispersed and attached to the multi-porous carbon nanofiber. The molybdenum-doped silicon-carbon composite material for a negative electrode of a lithium-ion battery of the present invention is prepared by the following steps.
[0023] (1) dissolving molybdenum acetylacetonate and polyacrylonitrile in N,N-dimethylformamide to obtain a first solution, and dissolving nano-silicon particles and polyacrylonitrile in N,N-dimethylformamide to obtain a second solution.
[0024] (2) The first solution and the second solution are mixed and stirred thoroughly to obtain a uniform mixed solution as a precursor solution for electrospinning.
[0025] (3) The electrospinning precursor solution is drawn out through a syringe equipped with a blunt-tipped needle, and a DC power supply is used to provide a voltage between the aluminum foil and the needle tip, causing the solution to be ejected from the metal needle and the material to be collected on the aluminum foil.
[0026] (4) The collected material is heated in a muffle furnace to degas and dry it.
[0027] (5) The degassed and dried material is taken out and calcined at high temperature in a tubular furnace, with argon as the protective gas during the calcination process.
[0028] (6) After the temperature of the tube furnace drops to room temperature, the calcined material is taken out to obtain a molybdenum-doped silicon-carbon composite material.
[0029] In step (2), in the mixed solution, the mass percentage concentration of molybdenum acetylacetonate is 0.5%-2%, the mass percentage concentration of polyacrylonitrile is 19%-44.75%, and the mass percentage concentration of nano-silicon particles is 10%-70%; the molecular weight of polyacrylonitrile is selected from any one of 100k, 150k, 200k, and 250K, preferably selected from any one of 100k, 150K, and 200k, and more preferably 150K.
[0030] In step (3), the feed rate of the electrospinning precursor solution is 0.1-5 ml / h, preferably 0.5-4.5 ml / min, more preferably 2-4 ml / min; the electrospinning height is 15-30 cm, preferably 16-29 cm, more preferably 18-26 cm; the electrospinning voltage is 15-25 kV, preferably 17-23 kV, more preferably 18-21 kV.
[0031] In step (4), the temperature of degassing and drying in the muffle furnace is 200°C-360°C, preferably 220°C-330°C, and more preferably 240°C-310°C.
[0032] In step (5), the calcination temperature in the tube furnace is 600°C-850°C, preferably 650°C-800°C, and more preferably 700°C-750°C.
[0033] Example 1
[0034] Weigh 0.5g of molybdenum acetylacetonate and 44.75g of 100K molecular weight polyacrylonitrile and dissolve them in 20ml of N,N-dimethylformamide to form a uniform solution, which is recorded as the first solution; weigh 10g of silicon nanoparticles and 44.75g of 100K molecular weight polyacrylonitrile and dissolve them in 20ml of N,N-dimethylformamide to form a uniform solution, which is recorded as the second solution. The first solution and the second solution are mixed, heated on a heating table and stirred to make them uniformly mixed to obtain a mixed solution, which is used as a precursor solution for electrospinning.
[0035] The electrospinning precursor solution prepared above was drawn out through a syringe equipped with a blunt needle, and then the needle was clamped with a stainless steel crocodile clip connected to a power supply, and aluminum foil was placed underneath to collect the electrospinning material; then a DC power supply was used to provide a voltage of 15 kV (i.e., the electrospinning voltage) between the aluminum foil and the tip of the needle, the distance between the aluminum foil and the tip of the needle (i.e., the electrospinning height) was 15 cm, and the feed rate was 0.1 ml / h; the solution was sprayed out from the metal needle, and the material was collected on the aluminum foil to obtain a molybdenum-doped silicon-carbon composite material precursor.
[0036] The molybdenum-doped silicon-carbon composite material precursor obtained above is placed in a muffle furnace for degassing and drying at 200°C, the degassed and dried material is taken out, and calcined at 600°C in a tubular furnace, with argon as the protective gas during the calcination process; after the temperature of the tubular furnace drops to room temperature, the calcined material is taken out to obtain a molybdenum-doped silicon-carbon composite material.
[0037] The following equipment was used to characterize the molybdenum-doped silicon-carbon composite material prepared above.
[0038] The material morphology was detected by scanning electron microscopy (SU8010). Figure 1 shown.
[0039] The element contents were detected by inductively coupled plasma optical emission spectrometry (Agilent 5800ICP-OES).
[0040] Half-cell performance test: Take 95 parts of the above molybdenum-doped porous silicon-carbon composite material, 2.5 parts of conductive additives, and 2.5 parts of binder, homogenize, coat, dry, and roll in an aqueous system to obtain a molybdenum-doped porous silicon-carbon negative electrode sheet. The above molybdenum-doped porous silicon-carbon negative electrode sheet is stacked with a diaphragm, a lithium sheet, and a stainless steel gasket in sequence, and 200 μL of electrolyte is added and sealed to form a 2016-type lithium-ion half-cell. The capacity and discharge efficiency are tested using a small (micro) current range device of Wuhan Blue Electric Electronics Co., Ltd.
[0041] The test results show that the mass percentage of molybdenum in the molybdenum-doped porous silicon-carbon composite material is 0.5%, and the mass percentage of silicon is 15%; the first cycle lithium removal capacity of the half-cell prepared by this material is 1622mAh / g, the first discharge efficiency of the half-cell is 88.5%, the full charge expansion is 85%, and the retention rate after 30 cycles is 70%. The results are shown in Table 1.
[0042] Example 2
[0043] Compared with Example 1, the differences are that the mass of molybdenum acetylacetonate is 0.6 g, the mass of silicon nanoparticles is 20 g; the voltage between the aluminum foil and the needle tip is 16 kV, the distance between the aluminum foil and the needle tip is 16 cm, and the feed rate is 0.5 ml / h; the degassing and drying temperature in the muffle furnace is 210°C, and the calcination in the tubular furnace is 620°C.
[0044] The test results show that the mass percentage of molybdenum in the molybdenum-doped porous silicon-carbon composite material is 0.6%, and the mass percentage of silicon is 20%; the first cycle lithium removal capacity of the half-cell prepared by this material is 1703mAh / g, the first discharge efficiency of the half-cell is 89.6%, the full charge expansion is 80%, and the retention rate after 30 cycles is 75%. The results are shown in Table 1.
[0045] Example 3
[0046] Compared with Example 1, the differences are that the mass of molybdenum acetylacetonate is 0.8 g, the mass of silicon nanoparticles is 30 g, and the molecular weight of polyacrylonitrile is 150K; the voltage between the aluminum foil and the needle tip is 17 kV, the distance between the aluminum foil and the needle tip is 18 cm, and the feed rate is 1.5 ml / h; the degassing and drying temperature in the muffle furnace is 220°C, and the calcination in the tubular furnace is 640°C.
[0047] The test results show that the mass percentage of molybdenum in the molybdenum-doped porous silicon-carbon composite material is 0.8%, and the mass percentage of silicon is 30%; the first-cycle lithium removal capacity of the half-cell prepared by this material is 1785mAh / g, the first discharge efficiency of the half-cell is 91.2%, the full charge expansion is 60%, and the retention rate after 30 cycles is 80%. The results are shown in Table 1.
[0048] Example 4
[0049] Compared with Example 1, the differences are that the mass of molybdenum acetylacetonate is 1 g, the mass of silicon nanoparticles is 40 g, and the molecular weight of polyacrylonitrile is 150K; the voltage between the aluminum foil and the needle tip is 18 kV, the distance between the aluminum foil and the needle tip is 20 cm, and the feed rate is 2 ml / h; the degassing and drying temperature in the muffle furnace is 240°C, and the calcination in the tubular furnace is 680°C.
[0050] The test results show that the mass percentage of molybdenum in the molybdenum-doped porous silicon-carbon composite material is 1%, and the mass percentage of silicon is 40%; the first-cycle lithium removal capacity of the half-cell prepared by this material is 1820mAh / g, the first discharge efficiency of the half-cell is 92.1%, the full charge expansion is 46%, and the retention rate after 30 cycles is 84%. The results are shown in Table 1.
[0051] Example 5
[0052] Compared with Example 1, the differences are that the mass of molybdenum acetylacetonate is 1.2 g, the mass of silicon nanoparticles is 50 g, and the molecular weight of polyacrylonitrile is 150K; the voltage between the aluminum foil and the needle tip is 19 kV, the distance between the aluminum foil and the needle tip is 23 cm, and the feed rate is 2.5 ml / h; the degassing and drying temperature in the muffle furnace is 260°C, and the calcination in the tubular furnace is 720°C.
[0053] The test results show that the mass percentage of molybdenum in the molybdenum-doped porous silicon-carbon composite material is 1.2%, and the mass percentage of silicon is 50%; the first-cycle lithium removal capacity of the half-cell prepared by this material is 1960mAh / g, the first discharge efficiency of the half-cell is 93.3%, the full charge expansion is 40%, and the retention rate after 30 cycles is 92%. The results are shown in Table 1.
[0054] Example 6
[0055] Compared with Example 1, the differences are that the mass of molybdenum acetylacetonate is 1.4 g, the mass of silicon nanoparticles is 55 g, and the molecular weight of polyacrylonitrile is 150K; the voltage between the aluminum foil and the needle tip is 20 kV, the distance between the aluminum foil and the needle tip is 24 cm, and the feed rate is 3 ml / h; the degassing and drying temperature in the muffle furnace is 280°C, and the calcination in the tubular furnace is 740°C.
[0056] The test results show that the mass percentage of molybdenum in the molybdenum-doped porous silicon-carbon composite material is 1.4%, and the mass percentage of silicon is 55%; the first-cycle lithium removal capacity of the half-cell prepared by this material is 1912mAh / g, the first discharge efficiency of the half-cell is 89.8%, the full charge expansion is 45%, and the retention rate after 30 cycles is 87%. The results are shown in Table 1.
[0057] Example 7
[0058] Compared with Example 1, the differences are that the mass of molybdenum acetylacetonate is 1.5 g, the mass of silicon nanoparticles is 58 g, and the molecular weight of polyacrylonitrile is 200K; the voltage between the aluminum foil and the needle tip is 21 kV, the distance between the aluminum foil and the needle tip is 26 cm, and the feed rate is 3.5 ml / h; the degassing and drying temperature in the muffle furnace is 300°C, and the calcination in the tubular furnace is 760°C.
[0059] The test results show that the mass percentage of molybdenum in the molybdenum-doped porous silicon-carbon composite material is 1.5%, and the mass percentage of silicon is 58%; the first-cycle lithium removal capacity of the half-cell prepared by this material is 1880mAh / g, the first discharge efficiency of the half-cell is 88.9%, the full charge expansion is 48%, and the retention rate after 30 cycles is 83%. The results are shown in Table 1.
[0060] Example 8
[0061] Compared with Example 1, the differences are that the mass of molybdenum acetylacetonate is 1.6 g, the mass of silicon nanoparticles is 60 g, and the molecular weight of polyacrylonitrile is 200K; the voltage between the aluminum foil and the needle tip is 22 kV, the distance between the aluminum foil and the needle tip is 27 cm, and the feed rate is 4 ml / h; the degassing and drying temperature in the muffle furnace is 320°C, and the calcination in the tubular furnace is 780°C.
[0062] The test results show that the mass percentage of molybdenum in the molybdenum-doped porous silicon-carbon composite material is 1.6%, and the mass percentage of silicon is 60%; the first-cycle lithium removal capacity of the half-cell prepared by this material is 1852mAh / g, the first discharge efficiency of the half-cell is 87.6%, the full charge expansion is 50%, and the retention rate after 30 cycles is 80%. The results are shown in Table 1.
[0063] Example 9
[0064] Compared with Example 1, the differences are that the mass of molybdenum acetylacetonate is 1.8 g, the mass of silicon nanoparticles is 65 g, and the molecular weight of polyacrylonitrile is 250K; the voltage between the aluminum foil and the needle tip is 24 kV, the distance between the aluminum foil and the needle tip is 28 cm, and the feed rate is 4.5 ml / h; the degassing and drying temperature in the muffle furnace is 340°C, and the calcination in the tubular furnace is 820°C.
[0065] The test results show that the mass percentage of molybdenum in the molybdenum-doped porous silicon-carbon composite material is 1.8%, and the mass percentage of silicon is 65%; the first-cycle lithium removal capacity of the half-cell prepared by this material is 1834mAh / g, the first discharge efficiency of the half-cell is 84.3%, the full charge expansion is 60%, and the retention rate after 30 cycles is 76%. The results are shown in Table 1.
[0066] Example 10
[0067] Compared with Example 1, the differences are that the mass of molybdenum acetylacetonate is 2 g, the mass of silicon nanoparticles is 70 g, and the molecular weight of polyacrylonitrile is 250K; the voltage between the aluminum foil and the needle tip is 25 kV, the distance between the aluminum foil and the needle tip is 30 cm, and the feed rate is 5 ml / h; the degassing and drying temperature in the muffle furnace is 360°C, and the calcination in the tubular furnace is 850°C.
[0068] The test results show that the mass percentage of molybdenum in the molybdenum-doped porous silicon-carbon composite material is 2%, and the mass percentage of silicon is 70%; the first-cycle lithium removal capacity of the half-cell prepared by this material is 1825mAh / g, the first discharge efficiency of the half-cell is 83.8%, the full charge expansion is 70%, and the retention rate after 30 cycles is 73%. The results are shown in Table 1.
[0069] Comparative Example 1
[0070] Compared with Example 1, the difference is that no molybdenum acetylacetonate is added in Comparative Example 1, and the other process conditions are the same.
[0071] The test results show that the mass percentage of molybdenum in the molybdenum-doped porous silicon-carbon composite material is 0%, and the mass percentage of silicon is 15.1%; the first-cycle lithium removal capacity of the half-cell prepared by this material is 1520mAh / g, the first discharge efficiency of the half-cell is 84.8%, the full charge expansion is 90%, and the retention rate after 30 cycles is 62%. The results are shown in Table 1.
[0072] Comparative Example 2
[0073] Compared with Example 1, Comparative Example 2 selects a traditional silicon-carbon synthesis process for preparation while keeping the amount of raw material added unchanged. The preparation method is as follows: 0.5 g of molybdenum acetylacetonate is added to the graphene solution and stirred to make it evenly dispersed; then 15 g of a silicon source (silicon monoxide) is added to the above solution, and the mixture is reacted in a high-pressure hydrothermal autoclave at 180°C and 3Mpa for 12 hours. After filtering and drying, a molybdenum-doped silicon-carbon composite material precursor is obtained; finally, the mixture is carbonized at 850°C to obtain a molybdenum-doped silicon-carbon composite material, the structure of which conforms to a multi-porous carbon nanostructure and has dispersed and attached silicon and molybdenum oxide nanoparticles.
[0074] The test results show that the molybdenum mass percentage of the molybdenum-doped silicon-carbon composite material prepared by the hydrothermal method is 0.5%, and the silicon mass percentage is 15%; the first cycle lithium removal capacity of the half-cell prepared by this material is 1580mAh / g, the first discharge efficiency of the half-cell is 84.5%, the full charge expansion is 86%, and the retention rate after 30 cycles is 60%. The results are shown in Table 1.
[0075] Table 1 Performance data of molybdenum-doped porous silicon-carbon composite materials and half-cells
[0076]
[0077] In summary, it can be seen from Example 1 to Example 10 in Table 1 that when the molybdenum content of the molybdenum-doped silicon-carbon material is 1.2%, the silicon content is 50%, and the polyacrylonitrile used is 150K molecular weight, the material prepared by electrostatic spinning has the best electrochemical performance, which has a discharge capacity of 1960mAh / g, a first coulomb efficiency of 93.3%, a full-charge expansion of 40%, and a 30-cycle capacity retention rate of 92%. By comparing Example 1 with Comparative Example 1, it can be seen that under the same electrostatic spinning process conditions, molybdenum doping brings improvements in electrochemical properties such as discharge capacity, first coulomb efficiency, full-charge expansion, and cycle retention rate to the material; by comparing the electrochemical properties of Example 1 with Comparative Example 2, it can be concluded that this electrostatic spinning preparation process is superior to the traditional hydrothermal preparation process. In summary, the composite material prepared by electrostatic spinning can not only improve the lithium storage activity, but also buffer the volume expansion of the silicon-carbon material during the lithium insertion and extraction process of the electrode, and improve the cycle stability of the material; in addition, the preparation method has the advantages of simple and easy operation, low cost, low energy consumption, and no pollution to the environment.
[0078] The above-mentioned technologies not specifically mentioned are all referred to the prior art.
[0079] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A molybdenum-doped silicon-carbon composite material for a negative electrode of a lithium-ion battery, characterized in that: The invention comprises multi-porous carbon nanofibers, silicon nanoparticles and molybdenum oxide nanoparticles, wherein the silicon nanoparticles and the molybdenum oxide nanoparticles are uniformly dispersed and attached to the multi-porous carbon nanofibers.
2. The molybdenum-doped silicon-carbon composite material for lithium-ion battery negative electrode according to claim 1, characterized in that: In the molybdenum-doped silicon-carbon composite material, the molybdenum content is 0.5%-2%, and the silicon content is 10%-70%, calculated by mass fraction.
3. The molybdenum-doped silicon-carbon composite material for lithium-ion battery negative electrode according to claim 2, characterized in that: In the molybdenum-doped silicon-carbon composite material, the molybdenum content is 0.7%-1.8%, and the silicon content is 15%-55%, calculated by mass fraction.
4. The molybdenum-doped silicon-carbon composite material for lithium-ion battery negative electrode according to claim 3, characterized in that: In the molybdenum-doped silicon-carbon composite material, the molybdenum content is 0.9%-1.6%, and the silicon content is 20%-50%, calculated by mass fraction.
5. The method for preparing the molybdenum-doped silicon-carbon composite material for lithium-ion battery negative electrode according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) dissolving molybdenum acetylacetonate and polyacrylonitrile in N,N-dimethylformamide to obtain a first solution, and dissolving nano-silicon particles and polyacrylonitrile in N,N-dimethylformamide to obtain a second solution; (2) mixing the first solution and the second solution and stirring them thoroughly to obtain a uniform mixed solution as a precursor solution for electrospinning; (3) The electrospinning precursor solution is drawn out through a syringe equipped with a blunt-tipped needle, and a DC power supply is used to provide a voltage between the aluminum foil and the needle tip, so that the solution is ejected from the metal needle and the material is collected on the aluminum foil; (4) The material collected on the aluminum foil is degassed, dried and calcined to obtain the product.
6. The method for preparing the molybdenum-doped silicon-carbon composite material for the negative electrode of a lithium-ion battery according to claim 5, characterized in that: In step (2), in the mixed solution, the mass percentage concentration of molybdenum acetylacetonate is 0.5%-2%, the mass percentage concentration of polyacrylonitrile is 19%-44.75%, and the mass percentage concentration of nano-silicon particles is 10%-70%; the molecular weight of polyacrylonitrile is selected from any one of 100K, 150K, 200K, and 250K; in step (3), the feed rate of the electrospinning precursor solution is 0.1-5ml / h, the electrospinning height is 15-30cm, and the electrospinning voltage is 15-25kV; in step (4), the degassing and drying temperature is 200℃-360℃; and the calcination temperature is 600℃-850℃.
7. An electrode, characterized in that: The invention relates to a molybdenum-doped silicon-carbon composite material for a negative electrode of a lithium-ion battery comprising the molybdenum-doped silicon-carbon composite material for a negative electrode of a lithium-ion battery according to any one of claims 1 to 4, or a molybdenum-doped silicon-carbon composite material for a negative electrode of a lithium-ion battery prepared by the method for preparing the molybdenum-doped silicon-carbon composite material for a negative electrode of a lithium-ion battery according to claim 5 or 6.
8. A battery, characterized in that: Comprising the electrode according to claim 7.